Comparison of pelvic floor muscle strength evaluations in nulliparous and primiparous women: a prospective study - Mônica Orsi Gameiro; Vanessa Oliveira Sousa; Luiz Felipe Gameiro; Rosana Carneiro Muchailh; Carlos Roberto Padovani; João Luiz Amaro (Clinics, 2011)
OBJECTIVE: This study aimed to compare the pelvic floor muscle strength of nulliparous and primiparous women. METHODS: A total of 100 women were prospectively distributed into two groups: Group 1 (G1) (n = 50) included healthy nulliparous women, and Group 2 (G2) (n = 50) included healthy primiparous women. Pelvic floor muscle strength was subjectively evaluated using transvaginal digital palpation. Pelvic floor muscle strength was objectively assessed using a portable perineometer. All of the parameters were evaluated simultaneously in G1 and were evaluated in G2 during the 20th and 36th weeks of pregnancy and 45 days after delivery. RESULTS: In G2, 14 women were excluded because they left the study before the follow-up evaluation. The median age was 23 years in G1 and 22 years in G2; there was no significant difference between the groups. The average body mass index was 21.7 kg/m² in G1 and 25.0 kg/m² in G2; there was a significant difference between the groups (p = 0.0004). In G2, transvaginal digital palpation evaluation showed significant impairments of pelvic floor muscle strength at the 36th week of pregnancy (p = 0.0006) and 45 days after vaginal delivery (p = 0.0001) compared to G1. Objective evaluations of pelvic floor muscle strength in G2 revealed a significant decrease 45 days after vaginal delivery compared to nulliparous patients. CONCLUSION: Pregnancy and vaginal delivery may cause weakness of the pelvic floor muscles.